Alkaloids from Lime Flower (Tiliae flos) Exert Spasmodic Activity on Murine Airway Smooth Muscle Involving Acetylcholinesterase - Hake, Alexander; Symma, Nico; Esch, Stefan; Hensel, Andreas; Düfer, Martina (Planta Medica, 2021)
Lime flower (Tiliae flos) is traditionally used either for treatment of the common cold or to relieve symptoms of mental stress. Recently, the presence of a new class of piperidine and dihydro-pyrrole alkaloids from lime flower has been described. The present study aimed to investigate the pharmacological activity of hydroacetonic lime flower extracts, alkaloid-enriched lime flower fractions, and isolated alkaloids on the murine airway smooth muscle and the cholinergic system. While a hydroacetonic lime flower extract did not show any pharmacological activity, enriched Tilia alkaloid fractions potentiated acetylcholine-induced contractions of the trachea by ~ 30%, showing characteristics comparable to galanthamine. Effects were abrogated by atropine, indicating an involvement of muscarinic receptors. The dihydro-pyrrole alkaloid tiliine A, the piperidine alkaloid tiliamine B, and the acetylated piperidine alkaloid tilacetine A were characterized as acetylcholinesterase inhibitors. The positive control galanthamine (IC50 = 2.0 µM, 95% CI 1.7 to 2.2 µM) was approximately 100 times more potent compared to tiliine A (IC50 = 237 µM, 95% CI 207 to 258 µM) and tiliamine B (IC50 = 172 µM, 95% CI 158 to 187 µM). Neither DNA synthesis of HepG2 liver cells, HaCaT keratinocytes, and Caco-2 intestinal epithelial cells nor cell viability of primary human fibroblasts was reduced by the alkaloids. The indirect cholinergic activity of the alkaloids might explain some aspects of the traditional use of lime flowers and may extend the portfolio of compounds with regard to diseases involving parasympathetic malfunction or central cholinergic imbalance.
Keywords: Tilia platyphyllos; Tilia cordata; Malvaceae; alkaloids; acetylcholinesterase inhibitor; tracheal smooth muscle